Expansion formulas in terms of integer-order derivatives for the Hadamard fractional integral and derivative - Pooseh, S. (2012)
We obtain series expansion formulas for the Hadamard fractional integral and fractional derivative of a smooth function. When considering finite sums only, an upper bound for the error is given. Numerical simulations show the efficiency of the approximation method.